Predictive Efficacy of the STOP-BANG Scoring System in Obstructive Sleep Apnea After Multilevel Airway Reconstructive Surgery: A Comprehensive Clinical Case Study Analysis - Fierda Ovita Azhari; Gustav Syukrinto (International Medical Journal Corp. Ltd, 2026)
Obstructive Sleep Apnea (OSA) is a sleep disorder characterized by recurrent collapse of the upper airway. The STOP-BANG questionnaire has been validated as a highly sensitive screening tool to identify surgical patients at high risk for OSA. This report aims to evaluate multilevel surgical management in a patient with a high STOP-BANG score and review the literature regarding its clinical efficacy. A 55-year-old male presented with chronic snoring, daytime fatigue, and witnessed apnea episodes over the last six months. Physical examination revealed a Body Mass Index (BMI) of 28.4 Kg/m2, a neck circumference of 45 cm, tonsillar hypertrophy, an elongated uvula, and turbinate hypertrophy. The patient's STOP-BANG score was 6, indicating a high risk for moderate-to-severe OSA. A STOP-BANG score ≥ 5 has a strong correlation with OSA severity and an increased risk of postoperative respiratory complications. Multilevel surgery is more effective than single-level procedures because it targets multiple collapse sites simultaneously (nasal and oropharyngeal). Integrating the STOP-BANG score into preoperative evaluations allows for accurate risk stratification. Multilevel surgery in well-selected patients can provide significant symptomatic improvement and reduce the long-term morbidity burden of OSA.